The Efficacy of an Extraoral Suction Apparatus on Reduction of Splatter Contamination during Impacted Lower Third Molar Surgical Procedure: An Observational Study - Surya Karthikeyan; Ravi Veeraraghavan; Jaeson Mohanan Painatt; Girisankar Manimangalath; Krishnaa Vijayan (Wolters Kluwer Medknow Publications, 2024)
Background: The COVID-19 pandemic has affected the delivery of dental care globally. Air contamination during aerosol and splatter-generating procedures is of great concern to dental healthcare provider during these times. Extra oral suction (EOS) apparatus has been shown to be effective in preventing infection by control of aerosol. But very limited data is available regarding the efficacy of the apparatus in preventing splatter contamination. Objectives of the Study: To assess the efficacy of EOS apparatus in reducing frequency and mean intensity of splatter contamination at clinician, assistant, patient sites during lower third molar surgical procedures. Materials and Methods: Patients who required surgical removal of an impacted lower third molar were divided into two groups (EOS and non-EOS) with 20 patients each. Universal indicating paper (UIP) was placed in specific locations on the surgeon, patient, and assistant. Colour changes after the settling of splatter on the UIP were analyzed to calculate the percentage intensity of splatter contamination. Results: The use of an EOS device has shown an overall reduction in the total number of contaminated sites, with a difference of 6.36%. Surgeon, patient, and assistant sites showed reductions of 6.25, 10%, and 1.66%, respectively. The apparatus has showed statistically significant reduction of splatter frequency and intensity at the patient's chest and left shoulder regions respectively, during surgical removal of the impacted 48. Conclusion: The magnitude of splatter contamination during minor dentoalveolar surgical procedures is inevitable. Therefore, to achieve a better working environment, usage of an EOS apparatus is advocated.